Histological Findings in Very Low Risk Prostate Cancer Patients Managed with Radical Prostatectomy (2017)
AbstractObjectives: To describe the histological findings in patients with prostate cancer (PCa) clinically classified as very low risk who underwent treatment with radical prostatectomy (RP). Material and methods: A retrospective observational study was conducted. Clinical records of patients who underwent RP between 2007-2015 who met Epstein criteria for very low risk disease were reviewed. Histological diagnosis was described and analyzed to determine if such criteria predicted very low risk. Results: A total of 609 records were reviewed; 83 (13.6%) met Epstein’s criteria. Mean age was 59 (SD±7) years and median PSA at diagnosis was 5.4 ng/dl (IQR 4.3 – 6.8). Pathology showed a median tumor volume of 4% (IQR 1 – 10%). Gleason score was 3+3 in 55 (66.3%) cases, but 28 (33.7%) were reclassified to a greater score. Two (2.4%) patients were reclassified as pT3a, 80 (96.4%) as pT2 and 1 (1.2%) was found to be pT0. In those subjected to pelvic lymphadenectomy (42.2%) no positive lymph nodes were found. Conclusions: Up to one-third of the patients clinically classified with very low risk PCa had a greater Gleason score. Only 3% had locally advanced tumors, which is comparable to previous studies. Epstein’s criteria seem to be adequate in predicting organ-confined disease.